Penile Metastasis From Prostate Cancer Detected by 18F-Fluorocholine PET/CT. (January 2021) - Bianchi, Denise; Rizzo, Alessio; Bonacina, Mattia; Zaniboni, Alberto; Savelli, Giordano
Abstract : Abstract: 18 F-Fluorocholine ( 18 F-FCH) PET/CT is widely used to study patients affected by prostate cancer. 18 F-FCH PET/CT is suitable for the detection of pelvic and abdominal nodal and skeletal metastases. Indeed, 18 F-FCH PET/CT sensitivity for other organs, such as the liver and the urinary tract, is lowered by the radiopharmaceutical urinary washout and intense liver uptake. Herein, we report the case of a patient affected by oligometastatic prostate cancer in good clinical condition treated with total androgen blockade. 18 F-FCH PET/CT showed a diffuse and intense uptake in the shaft of the penis, which was an evidence of a rare penile metastasis.